The relationship between conscientiousness, perceived partner support and work productivity associated with presenteeism between couples: the mediating role of housework engagement. - Leal, Ana Catarina; Ferreira, Aristides (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
This investigation aimed to study the relationships established between the variables conscientiousness, perceived partner support, housework engagement and work productivity associated with sickness presenteeism, based on the motivational process of job demands and resources theoretical model (JD-R; Bakker & Demerouti, 2007), among couples. The effects of housework on work productivity associated with sickness presenteeism are particularly relevant due to the visible inequalities that still exist between men and women, not only at work (Simpson, 1998), but also at home, specially on the distribution of domestic work (Rodrigues, Cunha & Wall, 2015). Hence, this study seeks to fill in literature gaps regarding the relationship between housework demands and resources and the phenomenon of sickness presenteeism. With a sample of 180 Portuguese heterosexual couples (N = 360), where both members of the couple were employed, an integrator model of house reality has been proposed. Therefore, we tested the effects of personal and social resources on work productivity associated with presenteeism, and the mediating effect of housework engagement, for both couple members. To test the formulated hypotheses two models were tested: one without mediation, and another with mediation, through structural equations modeling (SEM). Based on the results we verified that: (a) the higher the degree of women’s conscientiousness, the greater their level of productivity despite health problems; and (b) the higher the perception of partner support, the greater the level of work productivity, despite health problems, for both men and women. It was also possible to verify that housework engagement mediates the relationship between: (a) conscientiousness and work productivity despite health problems, for women; and (b) between perceived partner support and work productivity, despite health problems, for both couple members. These results provide a significant advance in the literature supporting the applicability of the JD-R model to housework. The study demonstrates that the availability of personal resources, and especially of social resources, such as partner support, can enable individuals to deal with demanding house tasks and fulfill them successfully, with less work productivity losses due to presenteeism. Consequently, we can affirm that the availability of personal and social resources can reduce productivity losses associated with feelings of exhaustion resulting from high work demands on both home and work domains. The results also allow to consider the existence of a positive side of presenteeism, especially for more conscientious individuals whose work productivity will be less affected when going to work experiencing minor health problems (Johns, 2010). Finally, the adaptation of the scales of the Survey of Perceived Organizational Support (SPOS-8: Eisenberger, Huntington, Hutchison & Sowa, 1986) and the Utrecht Work Engagement Scale (UWES-9: Schaufeli, Bakker & Salanova, 2006) for the family domain are also an important theoretical implication, hence they are useful tools for future studies that seek to study the family domain using the JD-R model. From an organizational point of view these results have important practical implications, showing how personality traits and family resources, such as partner support, can be managed by companies in order to turn them into important organizational advantages. At the end, study limitations and future research suggestions are also discussed.